DAMPAK KETERLIBATAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Grace, Ernest; Indajang, Kevin; Putra, Hendrick Sasimtan; Candra, Vivi; Simatupan, Sudung (Jurnal Ilmiah Global Education, 2023)
The ability of an organization to be able to achieve its goals cannot be separated from the ability of employees to always be involved in their work and apply work discipline that applies in the organization. The results of a study of civil servants of the Regional Secretariat of Samosir Regency as many as 118 people, using Slovin formula were obtained by respondents 91 employees. For instrument validity tests, valid results are found, while for reliability, reliable results are found. The equation of multiple regression found that work involvement and work discipline found a positive direction coefficient on employee performance with the results of the equation. Then for a partial test, it was found that employee involvement had a positive and significant influence on employee performance, the influence of work discipline on employee performance found positive and significant results on employee performance. Simultaneously, the results were obtained that work involvement and work discipline had a positive and significant effect on employee performance. When employees are always involved in their work and are able to follow all work disciplines applied by the organization, it will directly produce good performance as well.